Ocorrência e risco ecológico de hormônios estrogênios em efluentes urbanos e ambiente aquático receptor, Porto Seguro - Bahia - Silva, Rayanne Lima dos Santos (2025)
The natural estrogenic hormones Estrone (E1), 17ẞ-estradiol (E2), and Estriol (E3), as well as the synthetic hormone 17α-ethinylestradiol (EE2), are consistently found in the environment and pose serious risks to aquatic organisms and human health, even when detected at trace concentrations in the range of µg L-¹ and ngL-¹. These hormones can interfere with the natural functioning of the endocrine system in living organisms, causing various adverse effects. One of the main sources of these contaminants in the environment is the discharge of domestic effluents through Wastewater Treatment Plants (WWTPs), which are not designed to remove such pollutants. Given this context, the aim of this study is to determine the concentration of estrogenic hormones in samples of influent, effluent from sewage pumping stations, the municipal WWTP, and the receiving water body in Porto Seguro, Bahia; calculate the ecological risk of these contaminants for three aquatic organisms; and assess the impacts of hormone presence on the aquatic ecosystem. The target compounds were pre-concentrated using the Dispersive Micro-Solid Phase Extraction (D-µ-SPE) technique and simultaneously quantified by High-Performance Liquid Chromatography with Diode Array Detection (HPLC-DAD). In the influent, E3 concentrations ranged from <LOQ to 9.31 μg L-¹, E2 from <LOQ to 12.01 μg L-¹, EE2 from 0.26 to 8.62 μg L-¹, and E1 from <LOQ to 9.31 μg L-¹. In the treated effluent, only E2 (<LOQ to 0.21 µg L-¹) and EE2 (1.66 to 14.11 μg L-¹) were detected. In the river, E2 concentrations ranged from 0.33 to 3.31 µg L-¹ and EE2 from 3.23 to 8.51 µg L-¹. According to the ecological risk assessment, the concentrations of EE2 found in the river pose a high risk to three trophic levels of aquatic organisms-algae, daphnia, and fish. The E2 concentrations present a low to moderate risk for algae and daphnia, and a low to high risk for fish. The collection, monitoring, and interpretation of such data are important and may serve as a basis for implementing mitigation measures aimed at reducing the frequency and concentration of estrogens in regional rivers.